2019
DOI: 10.1097/prs.0000000000005903
|View full text |Cite
|
Sign up to set email alerts
|

Are 30-Day Outcomes Enough? Late Infectious Readmissions following Prosthetic-Based Breast Reconstruction

Abstract: Background: Surgical-site infection is a major concern in prosthetic-based breast reconstruction. Thirty-day postoperative readmission rates are a common quality metric, but little is known about readmission rates for later infections. Methods: Using the 2013 to 2014 Nationwide Readmissions Database, the authors identified breast cancer patients undergoing breast reconstruction with implants and tissue expanders who had an infectious readmission. The au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Despite these advances, infections, resulting in reconstructive failure, have a documented rate between 2.5% and 24%. 18 , 19 , 21 23 , 32 Khansa et al 20 and others 21 23 have published standardized best-practice protocols for preoperative, intraoperative, and postoperative measures to reduce infections. Despite following these protocols, we had a reconstructive failure rate secondary to infection of 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these advances, infections, resulting in reconstructive failure, have a documented rate between 2.5% and 24%. 18 , 19 , 21 23 , 32 Khansa et al 20 and others 21 23 have published standardized best-practice protocols for preoperative, intraoperative, and postoperative measures to reduce infections. Despite following these protocols, we had a reconstructive failure rate secondary to infection of 10%.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies evaluating postoperative complications and comorbidities associated with breast reconstructions [11][12][13][14][15][16][17][18], but only few have assessed the predictive risk factors for postoperative complications. It is common that only one or two surgical techniques are compared to or the follow-up time is 30 days postoperatively [14,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…It is common that only one or two surgical techniques are compared to or the follow-up time is 30 days postoperatively [14,19,20]. It has been concluded that traditional 30-day readmission rates are not an adequate quality metric for breast reconstruction given the number of late postoperative readmissions in breast reconstructions [11,18]. In order to describe reliable data concerning complications in breast reconstructive surgery, it is important to systematically analyze and compare complications from different reconstructive methods.…”
Section: Discussionmentioning
confidence: 99%
“…We advocate the early exchange approach for patients who require postmastectomy chemotherapy and radiotherapy because we feel these adjuvant treatments compromise healing and allow for indolent infections to eventually manifest. Radiotherapy and obesity have been demonstrated to be risk factors for late infections, 23 and our findings suggest a strategy that may help reduce this complication in these patients. We perform the exchange surgery 3 weeks after the mastectomy and TE placement and then allow for an additional 3 weeks of healing before chemotherapy or radiotherapy begins, because more significant delays in adjuvant treatment have been shown to decrease survival.…”
Section: Discussionmentioning
confidence: 52%
“…The low rates of infectious complications seen in the CG and EEG after second-stage exchange surgery in comparison with the higher rates observed after immediate reconstruction have been described by others. 23 , 33 …”
Section: Discussionmentioning
confidence: 99%